THE BREEDING OF LOCAL CORN BY MULTIGAMMA RADIATION METHOD (NUCLEAR) IN WEST TIMOR NUSA TENGGARA TIMUR - Pasangka, Bartholomeus (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Corn is one of Nusa Tenggara Timur main commodities. This plant has prospect to be increased in NTT, because it is adapted to the soil which has calcium deposits with relative low rainfall (dry soil) and high salinity. This research aimed to develop local corn variety through breeding by multi-gamma radiation method, selection, and crossing to obtain the prime seed of the local corn with different characteristics to its source plant.The method of research is breeding of local corn using gamma and multi-gamma radiation methods to produce several varieties of prime seed, so is very easy to select and obtain the prime seed of local corn. The other methods are comprised of observation, sampling, analysis, comparative, and interpretation.The result obtained on the first step (first year) is the selected mutation variety (the prime seed of local corn) with production 11 tons per ha (local yellow corn) and 9 tons per ha (local white corn). The production increase 36.4% (local yellow corn) and 33.3% (local white corn). On the second step (first year), obtained addition variety of selected mutation and more superior variety is resulted of crossing with production 13 tons per ha (local yellow corn) and 10 tons per ha (local white corn). The production increases 46.2% (local yellow corn) and 40.0% (local white corn). These results show that the breeding of local corn by multi-gamma radiation method and crossing can produce primer seed and has a certain quality to increase production significantly of the farmer on the sector of corn commodity.